Immunity priming and biostimulation by airborne nonanal increase yield of field-grown common bean plants - Elizarraraz-Martínez, Iris J.; Rojas-Raya, Mariana A.; Feregrino-Pérez, Ana A.; Partida-Martínez, Laila P.; Heil, Martin (Frontiers in Plant Science, 2024)
Introduction Stress-induced volatile organic compounds (VOCs) that induce plant immunity bear potential for biocontrol. Here, we explore the potential of nonanal to enhance the seed yield of common bean (Phaseolus vulgaris) under open field conditions that are realistic for smallholder farmers. Methods and results Using plastic cups with a nonanal-containing lanolin paste as low-cost dispensers, we observed that exposure of Flor de Junio Marcela (FJM) plants over 48h to airborne nonanal was followed by a 3-fold higher expression of pathogenesis-related (PR) genes PR1 and PR4. Both genes further increased their expression in response to subsequent challenge with the fungal pathogen Colletotrichum lindemuthianum. Therefore, we conclude that nonanal causes resistance gene priming. This effect was associated with ca. 2.5-fold lower infection rates and a 2-fold higher seed yield. Offspring of nonanal-exposed FJM plants exhibited a 10% higher emergence rate and a priming of PR1- and PR4-expression, which was associated with decreased infection by C. lindemuthianum and, ultimately, a ca. 3-fold increase in seed yield by anthracnose-infected offspring of nonanal-exposed plants. Seeds of nonanal-exposed and of challenged plants contained significantly more phenolic compounds (increase by ca 40%) and increased antioxidant and radical scavenging activity. Comparative studies including five widely used bean cultivars revealed 2-fold to 3-fold higher seed yield for nonanal-exposed plants. Finally, a cost-benefit analysis indicated a potential economic net profit of nonanal exposure for some, but not all cultivars. Outlook We consider nonanal as a promising candidate for an affordable tool that allows low-income smallholder farmers to increase the yield of an important staple-crop without using pesticides